Urban-Rural Disparities in Dental Services Utilization Among Adults in China's Megacities - Xiang Qi; Xiaomin Qu; Bei Wu (Frontiers Media S.A., 2021)
Objective: China's dental care system is bifurcated between urban and rural areas. However, very few studies have examined the dental services utilization inequities in China's megacities, particularly in these urban and rural areas. This study aims to examine the urban-rural disparities in dental services utilization among adults living in China's megacities based on the Andersen dental services utilization model.Methods: This study used data from 4,049 residents aged 18-65 who participated in the "2019 New Era and Living Conditions in Megacities Survey." Multivariate logistic regressions were employed to examine the associations between place of residence and dental services utilization for individuals from ten megacities in China. Predisposing variables (age, gender, marital status, living arrangement, and education), enabling variables (socioeconomic status, occupational status, income, insurance coverage, health attitude, and health behavior), and need variables (self-rated health, oral health status, gum bleeding) were controlled for.Results: The mean age of the 4,049 adults was 45.2 (standard deviation = 13.0), and 30.4% (n = 1,232) had no dental visits at all. Adults who resided in urban areas were more likely to use dental services [odds ratio (OR) = 1.57, 95% confidence interval (CI) = 1.30 to 1.91] than those residing in rural areas after controlling for key covariates. Factors associated with higher odds of visiting dentists include having a higher income (OR = 1.44, P < 0.001), higher education level (OR = 1.53, P = 0.042), being covered by insurance for urban residents/employees (OR = 1.49, P = 0.031), having a positive attitude toward healthy diets (OR = 1.43, P < 0.001), attending regular physical examination (OR = 1.66, P < 0.001), having more tooth loss (OR = 1.05, P < 0.001), and having frequent gum bleeding (OR = 2.29, P < 0.001).Conclusion: The findings confirm that place of residence is associated with dental services utilization while adjusting for key covariates. Despite rapid economic development in China, many adults had never visited dentists at all. More efforts should be taken to encourage widespread dental care, such as providing more dental coverage and better access to dental care services.